2011
DOI: 10.1159/000323926
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer: A Civilization Disorder

Abstract: Colorectal cancer arises in individuals with acquired or inherited genetic predisposition who are exposed to a range of risk factors. Many of these risk factors are associated with affluent Western societies. More than 95% of colorectal cancers are sporadic, arising in individuals without a significant hereditary risk. Geographic variation in the incidence of colorectal cancer is considerable with a higher incidence observed in the West. Environmental factors contribute substantially to this variation. A numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
156
0
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(174 citation statements)
references
References 124 publications
2
156
0
16
Order By: Relevance
“…In the previous studies; age, obesity, diabetes mellitus, family history, hereditary conditions, inflammatory bowel disease, diet (consumption of red and processed meat, diet low in fruits and vegetable), and lifestyle factors (physical activity, alcohol in-take, and smoking) were positively correlated with the risk of colorectal cancers (7,13,(15)(16)(17). It was also reported that longterm ulcerative colitis and Crohn's disease increases the risk of developing colorectal cancer (18,19).…”
Section: Original Article Aykan Et Al Epidemiology Of Colorectal Canmentioning
confidence: 92%
“…In the previous studies; age, obesity, diabetes mellitus, family history, hereditary conditions, inflammatory bowel disease, diet (consumption of red and processed meat, diet low in fruits and vegetable), and lifestyle factors (physical activity, alcohol in-take, and smoking) were positively correlated with the risk of colorectal cancers (7,13,(15)(16)(17). It was also reported that longterm ulcerative colitis and Crohn's disease increases the risk of developing colorectal cancer (18,19).…”
Section: Original Article Aykan Et Al Epidemiology Of Colorectal Canmentioning
confidence: 92%
“…Approximately 5% of all CRC cases are due to inherited genetic mutations, including many syndromes such as Familial Adenomatous Polyposis and Lynch syndrome (Power et al, 2010;Al-Sohaily et al, 2012); however, the vast majority of CRC cases have been linked to environmental causes rather than to heritable genetic changes (Lund et al, 2011;Watson and Collins, 2011). For many years, diet is recognized as an important factor in disease etiology and risk of CRC (Modan, 1977), including the consumption of red and processed red meat.…”
Section: Introductionmentioning
confidence: 99%
“…The inheritance determines individual susceptibility to sporadic cancer but the lifestyle and environmental exposures are necessary for cancer expression. Colorectal cancer incidence varies between different geographic regions and incidence and mortality rates have been highest in developed western nations (10,11). The basic argument that environment plays a huge role in colorectal cancer expression we get from observational studies in migrant populations.…”
Section: Etiology Of Colorectal Cancermentioning
confidence: 99%
“…Migrants from low-incident regions to the high-incident regions of North America within one generation accept the incidence of the host country. Yet, studies with migrants also suggest that geographic variation in colorectal cancer incidences is due to environmental exposures and not due to the inherent predisposition (racial and ethnic group) (1,10,11). Population based investigations have found many dietary and other environmental factors associated with colorectal cancer incidence (2).…”
Section: Etiology Of Colorectal Cancermentioning
confidence: 99%